CD4+NKG2D+ T cells exhibit enhanced migratory and encephalitogenic properties in neuroinflammation. - Tobias Ruck (Public Library of Science (PLoS), 2013)
Migration of encephalitogenic CD4(+) T lymphocytes across the blood-brain barrier is an essential step in the pathogenesis of multiple sclerosis (MS). We here demonstrate that expression of the co-stimulatory receptor NKG2D defines a subpopulation of CD4(+) T cells with elevated levels of markers for migration, activation, and cytolytic capacity especially when derived from MS patients. Furthermore, CD4(+)NKG2D(+) cells produce high levels of proinflammatory IFN-γ and IL-17 upon stimulation. NKG2D promotes the capacity of CD4(+)NKG2D(+) cells to migrate across endothelial cells in an in vitro model of the blood-brain barrier. CD4(+)NKG2D(+) T cells are enriched in the cerebrospinal fluid of MS patients, and a significant number of CD4(+) T cells in MS lesions coexpress NKG2D. We further elucidated the role of CD4(+)NKG2D(+) T cells in the mouse system. NKG2D blockade restricted central nervous system migration of T lymphocytes in vivo, leading to a significant decrease in the clinical and pathologic severity of experimental autoimmune encephalomyelitis, an animal model of MS. Blockade of NKG2D reduced killing of cultivated mouse oligodendrocytes by activated CD4(+) T cells. Taken together, we identify CD4(+)NKG2D(+) cells as a subpopulation of T helper cells with enhanced migratory, encephalitogenic and cytotoxic properties involved in inflammatory CNS lesion development.